Mining for Metabolites: A Study of Alternaria Species' - Villeneuve, Nicolas (Université d'Ottawa / University of Ottawa, 2021)
Over the past several years, fungal species’ (spp.) with the capability to infect humans have caused an estimated 1.6 million deaths annually, and are threatening bats, amphibians, and reptiles with extinction (Frick et al., 2010; Brown et al., 2012; Casadevall, 2017). Additionally, contamination of crops by fungal pathogens causes a loss of a third of all of the crops grown annually, thereby causing billions of dollars in economic losses on an annual basis (Fisher et al., 2012; Almeida et al., 2019). A common crop contaminant is the fungal genera comprised of many fungal pathogens, Alternaria. The overall objective of the present thesis was to use untargeted LC-MS metabolomics to further our understanding of their pathogenicity. Specifically, a robust profile for 60 strains of uncharacterized Alternaria spp. was generated which, when mined, revealed the presence of several unique secondary metabolites (SMs). Subsequent isolation, purification, and structural elucidation of those SMs revealed them to be the family of curvularins. Mining the genome of the isolates producing those curvularins revealed the biosynthetic gene cluster (BGC) necessary for the production of the curvularins. Generating sequence similarity networks (SSNs) allowed for the investigation of the similarity of the BGC necessary for the synthesis of the curvularins, across several pathogenic fungal spp.
Keywords: Metabolomics